Tinjauan Sistematis Efektivitas Pembelajaran Berbasis Etnosains dalam Meningkatkan Literasi Sains pada Pendidikan Dasar dan Menengah - Made Kartika Sari; I Wayan Suastra; I Nyoman Tika; I Wayan Redhana (Jurnal Penelitian Pendidikan IPA, 2025)
Conventional science learning often feels abstract and distant from students' realities, especially at the elementary and secondary levels. This can hinder the development of deep understanding and the relevance of the material to everyday life. Ethnoscience-based learning integrates local knowledge with modern scientific concepts to create contextual and meaningful learning. This study aims to: Assess the effectiveness of ethnoscience-based learning in improving students' scientific literacy at the elementary and secondary education levels; Identify learning models and media used in ethnoscience-based learning; Find challenges and supporting factors in implementing ethnoscience-based learning in schools. This study is a systematic review examining the effectiveness of ethnoscience-based learning in improving students' scientific literacy at the elementary and secondary levels. By analyzing 20 empirical studies published between 2020 and 2025, this review evaluated various learning models, teaching materials, and learning media that use ethnoscience as a foundation. The results show that ethnoscience-based learning consistently improves scientific literacy, critical thinking skills, learning motivation, and appreciation for local culture. Challenges such as limited teacher training and curriculum adjustments need to be addressed for optimal implementation. This study provides recommendations for developing more contextual curricula and learning practices, as well as strengthening teacher training. The findings are expected to serve as a reference for educators, researchers, and policymakers in strengthening scientific literacy through an ethnoscience approach.